Zur Frage über das Restglied im Zentralen Grenzwertsatz - Survila, P. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила, К вопросу об остаточном члене в центральной предельной теореме P. Survila, Liekamojo nario centrinėje ribinėje teoremoje klausimu